Spatiotemporal occurrence of beehives of genus Apis in Northern Punjab and Azad Jammu and Kashmir, Pakistan - Saira Bashir; Muhammad Faheem Malik; Mubashar Hussain (Kuwait Journal of Science)
Global insect pollinator declines in different landscapes have urged an increased need to assess the distribution and abundances of these pollinators in different landscapes. We explored seasonal patterns of occurrence of honeybees in selected districts of Northern Punjab (Sialkot, Gujrat, Gujranwala, Jhelum, and Rawalpindi) and associated two districts of AJK (Bhimber and Mirpur). We recorded the occurrence of beehives from agroforestry, cropped areas, and parks or tree plantations on monthly basis from 2019 to 2021. Taxonomic keys were used to identify the Apis spp. and consequently, beehives were recognized. Data were arranged seasonally i.e., Fall-Winter (September to February), Spring (March–May), and Summer (June–August). Data demonstrated significant differences (p ​< ​0.05) in the distribution patterns of beehives of Apis spp. among districts and seasons. In Jhelum and Bhimber districts, A. dorsata and A. cerana had a high percentage of hives as compared to A. florea but a lower percentage of hives was recorded in Sialkot and Gujranwala. A. dorsata had shown maximum occurrence in Jhelum (20.83%) than in Bhimber (14.52%) and Rawalpindi (16.41%). While A. cerana indicated a higher percentage of hives in Jhelum (20.95%) followed by Bhimber (17.74%), and Mirpur (14.53%). We detected that A. florea had a higher occurrence in Bhimber (16.61%), Sialkot (15.87%), and Jhelum (15.31%). The synthesis of our study suggests that A. dorsata may have greater occupancy in the areas with sub-mountainous topography. While there is a more generalized distribution of A. cerana and A. florea in plains like Sialkot, Gujranwala, and Gujrat. Based on our findings regarding their occurrence and coexistence, these three species have the potential to contribute to the honey production and genetic diversity of local flora in the study area.